Knowledge and Awareness of Amblyopia Among Families Attending Primary Care Clinics: A Cross-Sectional Study - Mohammed Mousa Almousa; Mustafa Kofi; Basil Khalid Alsahabi (Journal of Clinical Practice and Medical Research, 2026)
Background: Amblyopia causes lifelong monocular visual impairment when detection or treatment is delayed. Families influence screening and adherence, yet knowledge in primary care populations remains incompletely characterized. Objective: To assess objective and perceived amblyopia knowledge, identify associated factors, and examine agreement between self-rated and objectively scored knowledge among families attending primary care clinics. Methods: This cross-sectional survey analyzed 105 attendees from July 12–15, 2026. A nine-item instrument adapted from Basheikh et al. generated a 0–15 score; scores ≥8 indicated adequate knowledge. Confidence intervals, nonparametric tests, chi-square tests, false-discovery-rate correction, logistic regression, and agreement analyses were used. Results: The mean score was 6.30±3.31; median was 7 (IQR 4–9), and 43 participants (41.0%; 95% CI 32.0%–50.5%) had adequate knowledge. Internal consistency was acceptable (Cronbach’s α=.761). Fully adequate recognition was uncommon for causes (1.9%), symptoms (2.9%), risk factors (4.8%), and treatment (15.2%); 19.0% endorsed routine examinations as the appropriate time for an ophthalmic visit. Higher scores were associated with self-declared knowledge, having any information source, information-source category, a child’s prior amblyopia diagnosis, belief in curability with adherence, and recognition of parents’ treatment role (all false-discovery-rate q≤.005). Adequate knowledge was associated with self-declared knowledge, any information source, and a child’s prior diagnosis (all q=.017). The adjusted model was significant overall (likelihood-ratio χ2[5]=17.66, p=.003; AUC=.713), although no individual predictor was significant. Self-assessment showed fair agreement with objective adequacy (κ=.283). Conclusion: Knowledge was incomplete despite positive treatment attitudes. Primary care should deliver timely, effective, repeated education emphasizing asymptomatic disease, routine screening, causal pathways, and correct treatment.